Interhemispheric Lipoma, Callosal Anomaly, and Malformations of Cortical Development: A Case Series - Niwa, Tetsu; de Vries, Linda S.; Manten, Gwendolyn T. R.; Lequin, Maarten; Cuppen, Inge; Shibasaki, Jun; Aida, Noriko (Neuropediatrics, 2016)
Intracranial lipomas are rare congenital malformations. The most common type of intracranial lipoma is the interhemispheric lipoma, which is frequently associated with callosal anomalies such as hypogenesis or agenesis of the corpus callosum. In contrast, interhemispheric lipomas are less often accompanied with malformations of cortical development (MCD). We report magnetic resonance imaging findings of three infants with an interhemispheric lipoma, associated with a callosal anomaly, and MCD: two infants with nodular interhemispheric lipoma, agenesis of the corpus callosum, and polymicrogyria, and one infant with interhemispheric curvilinear lipoma, hypoplasia of the corpus callosum, and heterotopias. An association was suggested regarding the occurrence of these malformations.
Keywords: interhemispheric lipoma; callosal anomaly; malformations of cortical development; magnetic resonance imaging; infant